High-voltage aqueous planar symmetric sodium ion micro-batteries with superior performance at low-temperature of −40 ºC. (April 2021) - Wang, Xiao; Huang, Huijuan; Zhou, Feng; Das, Pratteek; Wen, Pengchao; Zheng, Shuanghao; Lu, Pengfei; Yu, Yan; Wu, Zhong-Shuai
Abstract: Aqueous sodium ion micro-batteries (ANIMBs) hold great promise in smart wearable microelectronics due to the abundant reserves, low cost and high safety of sodium. However, their applications are substantially hindered by the narrow electrochemical stability window of aqueous electrolytes within a limited temperature range. Herein, we report a prototype of high-voltage planar ANIMBs based on symmetric interdigital microelectrodes working in water-in-salt (WiS) electrolyte (17 M NaClO4 ) and displaying exceptional performance at low temperature. This work features nanoflower Na3 V2 (PO4 )3 (NVP)-based electrodes with perfectly matched voltage range as both anode and cathode in the WiS electrolyte operating in a widened electrochemical stability window (2.7 V vs. Na + /Na) under ultralow freezing point of −50 ºC. The resulting ANIMBs with interdigital in-plane geometry deliver remarkable volumetric capacity of 45 mAh/cm 3 and energy density of 77 mWh/cm 3, which are superior to most reported sodium-based micropower sources. Notably, the NVP||NaClO4 ||NVP micro-batteries exhibit a high coulombic efficiency of > 99% at room temperature down to −40 ºC. Furthermore, the NVP||NaClO4 ||NVP ANIMBs present admirable flexibility and modular integration. We believe that our ANIMBs can potentially enjoy wide market adoption ranging from domestic appliances to safe intelligent wearable microelectronics, especially those applications that need to be operated below freezing temperature. Graphical Abstract: High-voltage aqueous planar sodium ion micro-batteries with exceptional low-temperature performance are fabricated based on symmetric interdigital Na3 V2 (PO4 )3 microelectrodes, working in water-in-salt electrolyte of 17 M NaClO4, which exhibit high energy density of 77 mWh/cm 3, glorious integration in serial and parallel, and possess a splendid capacity retention of 88% at room temperature owing to outstanding resistance to the low-temperature at −40 ºC. ga1 Highlights: High-voltage aqueous sodium ion micro-batteries are constructed based on symmetric interdigital Na3 V2 (PO4 )3 microelectrode. The water-in-salt electrolyte of 17 M NaClO4 enables the micro-batteries with high energy density of 77 mWh/cm 3 . The planar micro-batteries possess splendid performance even under the low-temperature of –40 ºC.